Analysis of Human Resource Development in Improving Performance Efficiency in the Field of Public Information and Communication at the Department of Communication and Informatics of Ciamis Regency - Dita Dwi Nur'aeni; Ninis Dwi Rengganis; Rizal Ibrahim; Ii Sujai (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract In the midst of the globalization era and intense competition in the workforce, the quality of human resources (HR) becomes the main indicator in determining the quality of an organization, including government agencies. HR plays a vital role in supporting the success of organizational performance. The Communication and Informatics Office (Diskominfo) of Ciamis Regency is one of the agencies responsible for public services, especially through the Public Information and Communication Division. This division carries out several important tasks, such as: (1) providing cross-sectoral content and managing public communication media, (2) strengthening the capacity of public communication HR as well as providing access to information, and (3) coordinating technical activities, monitoring, and supervision in managing public opinion and aspirations within the regional government environment. Through these various tasks, it can be concluded that the presence of competent HR is crucial for the successful implementation of these duties, as it directly impacts the wider community in Ciamis Regency. However, in the Strategic Plan of Diskominfo Ciamis Regency for 2025–2026, it is mentioned that there is still a limitation in the number of HR with adequate qualifications to support the implementation of functions in the field of public information and communication. This problem becomes the main background of this study, which aims to analyze HR development in order to improve performance efficiency in that field. This study uses a qualitative approach with a case study method, and data collection techniques are carried out through observation, interviews, and documentation. Based on the results of four months of observation and interviews with Mr. Wahyu Widiartono, it was found that the quality of HR in the Public Information and Communication Division of Diskominfo Ciamis is already quite good, but still limited. This finding aligns with what has been stated in the Diskominfo Strategic Plan (RENSTRA) document for 2025–2026. Keywords: Human Resources, Institutional Quality Improvement, Communication and Informatics Office of Ciamis Regency